Filicide and Parental Separation and Divorce. (March 2014) - Brown, Thea; Tyson, Danielle; Arias, Paula Fernandez
<x xml:space="preserve">Abstract</x> This paper discusses the findings of a ten‐year study of filicide in Victoria, Australia, using the data from selected case files held in the Victorian coroner's office for the period 2000–09. The study sought to examine whether separation is a factor in filicide cases, as well as the role of other factors, such as domestic violence and mental illness. Also, the study sought to identify whether filicide perpetrators had contact with support services, including family and friends, general practitioners, mental health services and child protection services, in order to ascertain how these services might more appropriately identify those families most at risk prior to the filicide. The study found that while separation was a factor identified in a significant number of cases, more cases analysed showed evidence of mental illness, mainly depression. These findings suggest the need for improved strategies in preventing filicide by identifying risk factors and improving service responses for victims prior to these tragic events. Copyright © 2014 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2327-blk-0001" position="anchor" orientation="portrait"> 'While separation was a factor identified in a significant number of cases, more cases analysed showed evidence of mental illness, mainly depression' </boxed-text> Key Practitioner Messages: Filicide is uncommon but does occur. Perpetrators fall into three main groups and a different scenario is associated with each group. Associated (risk) factors were found to be mental illness (especially depression), separation, domestic violence and substance abuse. Any client/patient with mental illness and partner separation should be probed for thoughts of harm. Engagement with services is a protective factor.